Enzymatic determination of ethanol and glycerol by flow injection parallel multi-site detection - Rangel, António O. S. S. (2011)
A flow injection method was developed for the sequential enzymatic determination of ethanol and glycerol in wines, using immobilised ethanol dehydrogenase and glycerol dehydrogenase, respectively. The enzymes were immobilised separately on alkylaminated controlled pore glass. A multi-site spectrophotometric detection system was used in parallel configuration to monitor the absorbance change in the two independent analytical channels. A 50-fold dilution of the samples was necessary before injection. The working range was between 0.05 and 0.5% (v/v) for the ethanol and between 0.03 and 0.3 g l−1 for the glycerol determination, with corresponding detection limits of 2 10−3%(v/v) and 2 10−3 g l−1. Relative standard deviations (R.S.D.) (nD9) lower than 2.3% for the ethanol and 2.1% for the glycerol determination were found. For 13 samples of different types of table and Port wines, the results showed good agreement with the corresponding reference procedures; a two level recovery study also showed good accuracy for the developed methods. The sampling rate was 10 h−1, corresponding to 20 determinations per hour